Subversion of Host Innate Immunity by Human Papillomavirus Oncoproteins - Lo Cigno, Irene; Calati, Federica; Albertini, Silvia; Gariglio, Marisa (Pathogens (Basel), 2020)
The growth of human papillomavirus (HPV)-transformed cells depends on the ability of the viral oncoproteins E6 and E7, especially those from high-risk HPV16/18, to manipulate the signaling pathways involved in cell proliferation, cell death, and innate immunity. Emerging evidence indicates that E6/E7 inhibition reactivates the host innate immune response, reversing what until then was an unresponsive cellular state suitable for viral persistence and tumorigenesis. Given that the disruption of distinct mechanisms of immune evasion is an attractive strategy for cancer therapy, the race is on to gain a better understanding of E6/E7-induced immune escape and cancer progression. Here, we review recent literature on the interplay between E6/E7 and the innate immune signaling pathways cGAS/STING/TBK1, RIG-I/MAVS/TBK1, and Toll-like receptors (TLRs). The overall emerging picture is that E6 and E7 have evolved broad-spectrum mechanisms allowing for the simultaneous depletion of multiple rather than single innate immunity effectors. The cGAS/STING/TBK1 pathway appears to be the most heavily impacted, whereas the RIG-I/MAVS/TBK1, still partially functional in HPV-transformed cells, can be activated by the powerful RIG-I agonist M8, triggering the massive production of type I and III interferons (IFNs), which potentiates chemotherapy-mediated cell killing. Overall, the identification of novel therapeutic targets to restore the innate immune response in HPV-transformed cells could transform the way HPV-associated cancers are treated.